O Arquitecto como criador - diálogos entre artistas e arquitectos - João Pedro Teixeira Santos (2015)
Between Men only a few stand out in every gift simultaneously. From this category emerges the first division, which consists in selecting a few within a crowd. These ones, notable in wisdom, advices and intelligence, other ones experientes in the practical side of things, and other famous by the abundance and opulence of their fortunes. The scope of this thesis is to focus on showing how a fused cooperation between architects and artists in the same dialog could be advantagous, which alows to confer to the buildings and spaces not only a style but a unique character. This dissertation is divided in two parts: the first one splits in two segments and starts by analysing the influence of art in architecture in the vanguards of the 20th century and ends evidencing how positive it is the dialoge between artists and architects, based on two cases studies where this cooperation reveals the marked value of these collaborative and open processes. In the second part, I decided to find a different and interesting way of showing how this process happens. This is acomplished through the organization of the visual information in several and different frames that make obvious common traits and formal similarities between several works. This will lead to the dissolution between each other with the purpose of locating and enouncing the formal specific characterists of this connection. Finally, we can point out the results of the investigation, translated in important advantages which makes various fields of architectural design come to life.